2019
DOI: 10.14309/01.ajg.0000595812.94989.ac
|View full text |Cite
|
Sign up to set email alerts
|

1571 A Case of CMV Colitis Seen in DRESS

Abstract: INTRODUCTION: Cytomegalovirus (CMV) is a member of the family of herpes virus, which persists for life after a primary infection. It is known to cause colitis in both immunocompromised and immunocompetent hosts. This virus is prevalent in about 50%-80% of the general adult population. CMV enters a latency phase after initial infection. Reactivation can occur anywhere along the gastrointestinal tract. The colonic mucosa is the most common site of reactivation. Clinical, endoscopic, and histological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…12 The characteristic Owl's eye inclusion bodies are highly specific for CMV. 13 CMV colitis and IBD closely mimics each other in their clinical, endoscopic and histological appearance. Therefore, it is crucial to avoid misdiagnosis and mismanagement, keeping in mind the high morbidity associated with it.…”
Section: Discussionmentioning
confidence: 86%
“…12 The characteristic Owl's eye inclusion bodies are highly specific for CMV. 13 CMV colitis and IBD closely mimics each other in their clinical, endoscopic and histological appearance. Therefore, it is crucial to avoid misdiagnosis and mismanagement, keeping in mind the high morbidity associated with it.…”
Section: Discussionmentioning
confidence: 86%
“…Biopsy with immunohistochemistry using monoclonal antibodies against CMV antigens is now considered the gold standard 14 . The characteristic Owl's eye inclusion bodies are highly specific for CMV 15 . The human blood‐derived products (convalescent plasma, immunoglobulin) and immune‐modulatory therapies, like tocilizumab and corticosteroids, studied extensively for the treatment of severe SARS‐CoV‐2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…14 The characteristic Owl's eye inclusion bodies are highly specific for CMV. 15 The human blood-derived products (convalescent plasma, immunoglobulin) and immune-modulatory therapies, like tocilizumab and corticosteroids, studied extensively for the treatment of severe SARS-CoV-2 infection. In the RECOVERY trial, 16 dexamethasone therapy has shown a mortality benefit among COVID 19 patients who were requiring supplemental oxygen.…”
Section: Discussionmentioning
confidence: 99%